Pterostilbene reduces colonic inflammation by suppressing dendritic cell activation and promoting regulatory T cell development. Issue 11 (22nd September 2020) - Yashiro, Takuya; Yura, Shiori; Tobita, Akari; Toyoda, Yuki; Kasakura, Kazumi; Nishiyama, Chiharu
Abstract: Dendritic cells (DCs) and T cells play important roles in immune regulation, and modulating their function is an approach for developing preventive or therapeutic strategies against immune disorders. Herein, the effect of pterostilbene (PSB) (3′, 5′‐dimethoxy‐resveratrol)—a resveratrol‐related polyphenol found in blueberries—on immune regulation was evaluated. Using an in vitro co‐culture system, PSB was found to exert the strongest inhibitory effect among all tested resveratrol derivatives on DC‐mediated T cell proliferation; moreover, PSB treatment decreased the Th1 and Th17 populations and increased the regulatory T cell (Treg) population. Upon co‐stimulation with anti‐CD3 and anti‐CD28 antibodies, PSB inhibited CD4 + T cell proliferation and differentiation into Th1 cells. Additionally, PSB acted on DCs to suppress the lipopolysaccharide‐induced transactivation of genes encoding antigen presentation‐related molecules and inflammatory cytokines by attenuating the DNA‐binding ability of the transcription factor PU.1. Furthermore, PSB promoted DC‐mediated Foxp3 + Treg differentiation, and PU.1 knockdown increased DC‐induced Treg activity. Oral administration of PSB alleviated the symptoms of dextran sulfate sodium‐induced colitis and decreased tumor necrosis factor‐α expression in mice. Thus, PSB treatment ameliorates colonic inflammation.